Sexuality and gender now : moving beyond heteronormativity - Hertzmann, Leezah, 1963-; Newbigin, Juliet, 1948- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2019)
Sexuality and Gender Now uses a psychoanalytic approach to arrive at a more informed view of the experience and relationships of those whose sexuality and gender may not align with the heterosexual "norm". This book confronts the heteronormative bias dominant in psychoanalysis, using a combination of theoretical and clinical material, offering an important training tool as well as being relevant for practicing clinicians. The contributors address the shift clinicians must make not only to support their patients in a more informed and non-prejudicial way, but also to recognise their own need for support in developing their clinical thinking. They challenge assumptions, deconstruct theoretical ideas, extend psychoanalytic concepts, and, importantly, show how clinicians can attend to their pre-conscious assumptions. They also explore the issue of erotic transference and countertransference, which, if unaddressed, can limit the possibilities for supporting patients more fully to explore their sexuality and gender. Theories of psychosexuality have tended to become split off from the main field of psychoanalytic thought and practice or read from an assumed moral high ground of heteronormativity. The book specifically addresses this bias and introduces new ways of using psychoanalytic ideas. The contributors advocate a wider and more flexible attitude to sexuality in general, which can illuminate an understanding of all sexualities, including heterosexuality. Sexuality and Gender Now will be essential reading for professionals and students of psychoanalysis who want to broaden their understanding of sexuality and gender in their clinical practice beyond heteronormative assumptions.
Sex and the consulting room -- Homophobia, heteronormativity and shame -- Working with sameness and difference: reflections on supervision with diverse sexualities -- Desire -- Losing the internal Oedipal mother and loss of sexual desire -- The primary maternal Oedipal situation and female homoerotic desire -- Mending the symbolic, when a place for male same-sex desire is not found -- Perspectives on gender -- From bisexuality to intersexuality: rethinking gender categories -- Notes on a crisis of meaning in the care of gender diverse children -- Crossing over -- Gender now -- Anonymous: a person beyond gender.
OCLC-licensed vendor bibliographic record.
Keywords: Sexual minorities -- Mental health; Sexual minorities -- Counseling of; Sexual orientation -- Psychological aspects; Sex role -- Psychological aspects; Cultural psychiatry; Psychotherapy; PSYCHOLOGY / Movements / Psychoanalysis; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health